Predictive Factors for Postoperative Opioid Use in Elective Skull Base Craniotomies - Potter, Tamia; Soni, Pranay; Krywyj, Maria; Obiri-Yeboah, Derrick; Oyem, Precious; Momin, Arbaz; Easley, Kathryn; Recinos, Pablo F.; Kshettry, Varun R. (Journal of Neurological Surgery Part B: Skull Base, 2022)
Objective In 2017, the United States officially declared opioid overuse a public health emergency. Due to a paucity of published benchmark data in skull base neurosurgery, we quantified postoperative opioid use in patients undergoing skull base craniotomies and identified factors that influence postoperative opioid use.Setting Tertiary academic medical center.Participants Patients who underwent elective craniotomies by two skull base neurosurgeons between January 2015 and May 2020.Main Outcome Measures Demographic and perioperative data were retrospectively extracted from the electronic medical record. Surgical approaches were categorized as having either “significant” or “minimal” muscle dissection. Univariate and multivariate linear regression analyses were performed to identify predictors of postoperative opioid use at 24, 48, and 72 hours.Results We included 300 craniotomies, 206 were supratentorial and 94 were infratentorial. This included 195 women and 105 men, with a mean age of 54.9 years. In multivariable analysis, a history of anxiety or depression, preoperative opioid use, and a history of migraines independently predicted a significantly greater opioid use at 24, 48, and 72 hours. Increased age and minimal muscle dissection independently predicted lower opioid consumption. Sex, infratentorial versus supratentorial approach, length of surgery, and postoperative steroid use did not impact total opioid use.Conclusion Younger age, history of anxiety or depression, preoperative opioid consumption, preexisting history of migraines, and significant intraoperative muscle dissection were associated with higher postoperative opioid consumption. These risk factors provide insight on potential targets for minimizing postoperative opioids in craniotomies.
Keywords: opioid; craniotomy; skull base; pain